PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI SD - DRANSI, FELLY (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study on the basis the low student learning outcomes because teacher still use the lecture method whict makes students bored.learning activities are rooted in th lack of teachers leat students in a learning activity.To fill the weaknesses that accur in teching during these teachers make learning sciene research usiang a contextual teaching and learning (CTL) approach in teaching.This research is action research (class action research),research using qualitative and quanlitative approaches.The procedure consisted of the planning stage,the implementation stage,the stage of observation,and reflection phase.The study uses CTL approach can improve student learning outcomes.Average values of student in the first cycle after a combined 68.18 kognitif three aspects,affective and psychomotor percentage of completeness with 66.34 % of studends in the first cycle,while there is increased after extensive reflection by value-average students is 86.58 after combined three aspects kognitif,affective and psychomotor mastery percentage of students with 85.26% of the students completed.   Kata Kunci : hasil belajar,pembelajaran IPA, contextual teaching and learning(ctl)